Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Media Objek Langsung pada Mata Pelajaran Bahasa Indonesia Tingkat Madrasah Ibtidaiyah - Nurannisa, Rizki; Tantowie, Tanto Aljauharie; Dudi, Dudi (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
Learning Indonesian especially in the ability to write simple essays in class II SDN 2 Sukasenang Sindangkasih Subdistrict, Ciamis District with environmental teaching materials around the school provides opportunities for students to be active, creative, and critical. In general, the results of appropriate studies can significantly meet the needs of teachers and students in which standard learning procedures. The ability of students to write simple essays using direct objects in the first cycle of meeting 1 was 73.51; the second cycle of meeting 1 amounted to 82.5; the second cycle of meeting 2 was 82.96; the third cycle of meeting 1 was 87.6; the second cycle of the second meeting was 91.35. 2) The skills of teachers in teaching in the first cycle of meeting 1 amounted to 79.8; the second cycle of meeting 1 was 80.4; the second cycle of meeting 2 was 81.7; the third cycle of meeting 1 was 85.1; the second cycle of meeting 2 was 89.82. 3) Student learning outcomes in the first cycle of meeting 1 amounted to 64.17; the second cycle of meeting 1 was 67.69; the second cycle of meeting 2 was 71.13; the third cycle of meeting 1 was 78.4; the third cycle of meeting 2 was 81.8. The ability of students to write an essay description using a direct object seems to have an increase even though it is not maximal. Increasing the ability of students to write essays using direct objects can be seen from changes in the average value of each aspect of writing essays in a better direction. This proves that media objects can directly improve student learning outcomes on the theme of safety at home and on the journey Indonesian language is the subject of essay writing at SD Negeri 2 Sukasenang. The results of the analysis indicate that the proposed hypothesis is acceptable